Global, regional, and national causes of child mortality in 2000–13, with projections to inform post-2015 priorities: an updated systematic analysis. Issue 9966 (31st January 2015) - Liu, Li; Oza, Shefali; Hogan, Daniel; Perin, Jamie; Rudan, Igor; Lawn, Joy E; Cousens, Simon; Mathers, Colin; Black, Robert E
Summary: Background: Trend data for causes of child death are crucial to inform priorities for improving child survival by and beyond 2015. We report child mortality by cause estimates in 2000–13, and cause-specific mortality scenarios to 2030 and 2035. Methods: We estimated the distributions of causes of child mortality separately for neonates and children aged 1–59 months. To generate cause-specific mortality fractions, we included new vital registration and verbal autopsy data. We used vital registration data in countries with adequate registration systems. We applied vital registration-based multicause models for countries with low under-5 mortality but inadequate vital registration, and updated verbal autopsy-based multicause models for high mortality countries. We used updated numbers of child deaths to derive numbers of deaths by causes. We applied two scenarios to derive cause-specific mortality in 2030 and 2035. Findings: Of the 6·3 million children who died before age 5 years in 2013, 51·8% (3·257 million) died of infectious causes and 44% (2·761 million) died in the neonatal period. The three leading causes are preterm birth complications (0·965 million [15·4%, uncertainty range (UR) 9·8−24·5]; UR 0·615–1·537 million), pneumonia (0·935 million [14·9%, 13·0–16·8]; 0·817–1·057 million), and intrapartum-related complications (0·662 million [10·5%, 6·7–16·8]; 0·421–1·054 million). Reductions in pneumonia, diarrhoea, and measles collectively were responsible for half of the 3·6 million fewer deaths recorded in 2013 versus 2000. Causes with the slowest progress were congenital, preterm, neonatal sepsis, injury, and other causes. If present trends continue, 4·4 million children younger than 5 years will still die in 2030. Furthermore, sub-Saharan Africa will have 33% of the births and 60% of the deaths in 2030, compared with 25% and 50% in 2013, respectively. Interpretation: Our projection results provide concrete examples of how the distribution of child causes of deaths could look in 15–20 years to inform priority setting in the post-2015 era. More evidence is needed about shifts in timing, causes, and places of under-5 deaths to inform child survival agendas by and beyond 2015, to end preventable child deaths in a generation, and to count and account for every newborn and every child. Funding: Bill & Melinda Gates Foundation.